Modified polypropylene material as well as preparation method and application thereof

Through the combination of mesoporous titanium dioxide-loaded silver zinc ions and high-modulus polypropylene resin, the problem of difficult to take into account both the antibacterial and scratch resistance of polypropylene materials is achieved, and high-efficiency and long-lasting antibacterial effects and excellent mechanical properties are achieved. Automobile interior parts.

CN119241946APending Publication Date: 2025-01-03GUANGDONG JUSHI CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411376677.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

While improving antibacterial and mechanical properties, existing polypropylene materials are difficult to maintain scratch resistance. Excessive addition of commonly used antibacterial agents will affect the mechanical properties of the material, especially in automotive interior parts.

Method used

Mesoporous titanium dioxide-loaded silver ions and zinc ions are used as composite antibacterial agents, and the antibacterial performance is improved through pressurized treatment, combining high-modulus polypropylene resin and spherical inorganic filler to reduce the amount of scratch-resistant agent, enhance the mechanical properties of the material and antibacterial Effect.

Benefits of technology

It has achieved that polypropylene materials have excellent antibacterial properties and scratch resistance without increasing the amount of antibacterial agent, extend their service life, and have good application prospects in automotive interior parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068844990000111
    Figure BDA0005068844990000111
  • Figure BDA0005068844990000112
    Figure BDA0005068844990000112
  • Figure BDA0005068844990000121
    Figure BDA0005068844990000121
Patent Text Reader

Abstract

The invention discloses a modified polypropylene material as well as a preparation method and application thereof. The modified polypropylene material comprises the following preparation raw materials in parts by mass: 50-90 parts of polypropylene resin; 5-25 parts of a filler; 1-6 parts of a compatilizer; 0.5 to 3 parts of a scratch resistant agent; 0.5-2 parts of a composite antibacterial agent; 0.1-2 parts of a functional auxiliary agent; the bending modulus of the polypropylene resin is greater than or equal to 1900MPa; the composite antibacterial agent comprises mesoporous titanium dioxide, and silver ions and / or zinc ions are loaded in a mesoporous structure of the mesoporous titanium dioxide; the pore diameter of the mesoporous titanium dioxide is 1-15 nm, and the pore volume of the mesoporous titanium dioxide is 15-40 m < 3 > / g. The high-modulus polypropylene resin is selected as a base material, and the composite antibacterial agent, the spherical inorganic filler and other raw materials are combined, so that the material has excellent mechanical properties and scratch resistance while maintaining efficient and lasting antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a modified polypropylene material and a preparation method and application thereof. Background Art

[0002] Polypropylene (PP) is a commonly used thermoplastic in daily life. It is widely used due to its low cost, low density, and easy processing. However, as people's requirements for material performance continue to increase, polypropylene materials with a single performance have been unable to meet the diverse market needs. Polypropylene materials are easily affected by scratches, wear and other factors in daily use, resulting in a decrease in surface quality, affecting appearance and service life. This is especially important for automotive parts that are easily in contact with hard objects, such as car armrests. Improving the scratch resistance of polypropylene products is particularly important.

[0003] In addition, due to the molecular structure characteristics of the polypropylene material itself, it is easy to adhere to bacteria, especially in parts such as car armrests and handles that are in direct contact with the human body, which will cause certain harm to human health. The method of adding antibacterial agents to polypropylene materials is generally adopted in the prior art, so that the polypropylene material obtains the corresponding antibacterial effect. However, the commonly used antibacterial agents are prepared by loading metal ion antibacterial agents (such as silver ions, zinc ions, and copper ions) with zeolite, glass beads, and silica as the matrix. However, the matrix of this antibacterial agent itself does not have antibacterial properties, and the loading rate of metal ions such as silver and zinc is low. Therefore, if you want to achieve an ideal antibacterial effect, you must add a large amount of antibacterial agents, but adding excessive antibacterial agents will have a greater negative impact on the mechanical properties of polypropylene. An antibacterial polypropylene material is disclosed in the prior art, which needs to add 5 parts of inorganic antibacterial agents to achieve a better antibacterial effect. The addition of this excessive antibacterial agent will greatly reduce the mechanical properties of the polypropylene material.

[0004] Therefore, how to maintain the excellent antibacterial and mechanical properties of polypropylene and improve the scratch resistance of polypropylene without adding excessive antibacterial agents is of great significance for expanding the application of polypropylene materials in high-end fields such as automotive interiors. Summary of the invention

[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a modified polypropylene material, which does not require the addition of excessive antibacterial agent (the added mass parts are 2 parts or less), thereby ensuring that the polypropylene material has excellent antibacterial properties and mechanical properties, and can also improve the scratch resistance of the polypropylene material, extend the service life of the material and protect human health.

[0006] A second object of the present invention is to provide a method for preparing the modified polypropylene material.

[0007] The third object of the present invention is to provide an application of the modified polypropylene material.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a modified polypropylene material, comprising the following raw materials in parts by weight: 50 to 90 parts of polypropylene resin; 5 to 25 parts of filler; 1 to 6 parts of compatibilizer; 0.5 to 3 parts of anti-scratch agent; 0.5 to 2 parts of composite antibacterial agent; 0.1 to 2 parts of functional additive;

[0010] The flexural modulus of the polypropylene resin is ≥1900MPa;

[0011] The filler includes a spherical inorganic filler;

[0012] The composite antibacterial agent comprises mesoporous titanium dioxide, and the mesoporous structure of the mesoporous titanium dioxide is loaded with silver ions and / or zinc ions; the pore size of the mesoporous titanium dioxide is 1 to 15 nm, and the pore volume of the mesoporous titanium dioxide is 15 to 40 m 3 / g.

[0013] In some specific embodiments of the present invention, the testing standard for the flexural modulus is ASTM D790-2017.

[0014] In some specific embodiments of the present invention, the silver ion content in the composite antibacterial agent is 9-16wt%.

[0015] In some specific embodiments of the present invention, the zinc ion content in the composite antibacterial agent is 14-20wt%.

[0016] In some specific embodiments of the present invention, the composite antibacterial agent is prepared by a method comprising the following steps: mixing silver salt and / or zinc salt with mesoporous titanium dioxide, and then subjecting the mixture to pressure treatment to obtain the composite antibacterial agent.

[0017] In some specific embodiments of the present invention, the pressure of the pressurization treatment is 6-14 MPa.

[0018] In some specific embodiments of the present invention, the temperature of the pressure treatment is 60-140°C.

[0019] In some specific embodiments of the present invention, the time of the pressure treatment is 2 to 10 hours.

[0020] In some specific embodiments of the present invention, the anti-scratch agent includes an amide anti-scratch agent, a silicone anti-scratch agent or a combination thereof.

[0021] In some specific embodiments of the present invention, the average particle size of the spherical inorganic filler is 400-700 nm.

[0022] In some specific embodiments of the present invention, the density of the spherical inorganic filler is 0.5 to 3 g / cm 3 .

[0023] In some specific embodiments of the present invention, the spherical inorganic filler includes at least one of calcium carbonate, glass beads, silicon dioxide, boron nitride, silicate, aluminum oxide or titanium dioxide.

[0024] In some specific embodiments of the present invention, the filler further comprises a non-spherical inorganic filler.

[0025] In some specific embodiments of the present invention, the non-spherical inorganic filler includes talc, silica fume or a combination thereof.

[0026] In some embodiments of the present invention, the compatibilizer includes a maleic anhydride grafted polymer.

[0027] In some specific embodiments of the present invention, the maleic anhydride grafting rate of the maleic anhydride grafted polymer is 0.8 to 2.5 wt %.

[0028] In some specific embodiments of the present invention, the maleic anhydride grafted polymer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene or maleic anhydride grafted polyolefin elastomer.

[0029] In some specific embodiments of the present invention, the functional auxiliary agent includes an antioxidant, a lubricant or a combination thereof.

[0030] In some specific embodiments of the present invention, the amount of the antioxidant is selected from 0.05 to 1 part by mass.

[0031] In some specific embodiments of the present invention, the amount of the lubricant is selected from 0.05 to 1 part by mass.

[0032] The second aspect of the present invention provides a method for preparing the modified polypropylene material described in the first aspect of the present invention, comprising the following steps: mixing other preparation raw materials of the modified polypropylene material except the filler, adding the mixture to the main feed port of a twin-screw extruder, adding the filler to the side feed port of the twin-screw extruder, and extruding to obtain the modified polypropylene material.

[0033] The third aspect of the present invention provides a use of the modified polypropylene material described in the first aspect of the present invention in the preparation of automobile parts.

[0034] The beneficial effects of the present invention are as follows: the present invention selects high modulus polypropylene resin as a base material, and can reduce the amount of the scratch resistance agent while maintaining the scratch resistance; the composite antibacterial agent of the present invention is used to make the material have a high antibacterial rate, and will not affect the mechanical properties of the polypropylene material; combined with raw materials such as spherical inorganic fillers, it is beneficial to make the material have a high-efficiency and lasting antibacterial effect, and excellent mechanical properties and scratch resistance. The modified polypropylene material provided by the present invention has a long service life and a good antibacterial effect, can avoid harm to human health, and has good application prospects in automobile parts, especially automobile interiors.

[0035] Specifically, compared with the prior art, the present invention has the following advantages:

[0036] 1. The present invention utilizes nano-scale mesoporous titanium dioxide to load Ag + With Zn 2+ A composite antibacterial agent was prepared, in which titanium dioxide itself has antibacterial properties and is then combined with an inorganic antibacterial agent Ag. + With Zn 2+ After the combination, the antibacterial performance is further improved; in addition, the use of mesoporous titanium dioxide and pressurization can make more Ag + With Zn 2+ Loaded inside the mesoporous titanium dioxide particles, Ag + With Zn 2+ It will be slowly released through the mesopores on the surface of titanium dioxide to achieve the purpose of high efficiency and long-lasting antibacterial effect.

[0037] 2. High modulus polypropylene itself has high hardness and scratch resistance. The present invention uses high modulus polypropylene resin as the base material, which can reduce the amount of scratch resistance while maintaining scratch resistance; mesoporous titanium dioxide with appropriate pore size and pore volume is conducive to improving the antibacterial rate and long-term antibacterial effect of the material, and the use of mesoporous titanium dioxide in combination with silver salt and zinc salt has a higher antibacterial rate, so that only a small amount of composite antibacterial agent is needed to make the polypropylene material achieve excellent antibacterial performance without reducing the mechanical properties of the polypropylene material; spherical inorganic fillers are used to make them more effectively dispersed in the base material, forming a more uniform and dense composite structure, and obtaining a material with higher strength; combined with maleic anhydride grafted polymer compatibilizer and silicone scratch resistance agent, the mechanical properties and scratch resistance of the material can be further improved.

[0038] 3. The modified polypropylene material prepared by the present invention is an antibacterial, scratch-resistant, high-modulus polypropylene material, which has a high-efficiency and lasting antibacterial effect, and has excellent mechanical properties and scratch resistance, can extend the service life of the product, and can avoid harm to human health. It has good application prospects in automotive parts, especially automotive interiors. DETAILED DESCRIPTION

[0039] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0040] The first aspect of the embodiment of the present invention provides a modified polypropylene material, comprising the following raw materials in parts by weight: 50 to 90 parts of polypropylene resin; 5 to 25 parts of filler; 1 to 6 parts of compatibilizer; 0.5 to 3 parts of anti-scratch agent; 0.5 to 2 parts of composite antibacterial agent; 0.1 to 2 parts of functional additive;

[0041] The bending modulus of polypropylene resin is ≥1900MPa;

[0042] Fillers include spherical inorganic fillers;

[0043] The composite antibacterial agent comprises mesoporous titanium dioxide, and the mesoporous structure of the mesoporous titanium dioxide is loaded with silver ions and / or zinc ions; the pore size of the mesoporous titanium dioxide is 1 to 15 nm, and the pore volume of the mesoporous titanium dioxide is 15 to 40 m 3 / g.

[0044] In some embodiments of the present invention, the testing standard for flexural modulus is ASTM D790-2017.

[0045] In some embodiments of the present invention, the flexural modulus of the polypropylene resin is 1900-5000 MPa; in some specific embodiments of the present invention, the flexural modulus of the polypropylene resin is 2000-4000 MPa; in some examples of the present invention, the flexural modulus of the polypropylene resin is 2100-3000 MPa. Non-limiting specific examples are 2200 MPa, 2300 MPa, 2500 MPa, 2700 MPa or 2900 MPa.

[0046] In some embodiments of the present invention, the melt index of the polypropylene resin at 230°C and 2.16 kg is 5 to 30 g / 10 min; in some specific embodiments of the present invention, the melt index of the polypropylene resin at 230°C and 2.16 kg is 8 to 25 g / 10 min; in some examples of the present invention, the melt index of the polypropylene resin at 230°C and 2.16 kg is 10 to 20 g / 10 min. Non-limiting specific examples include 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, or 18 g / 10 min.

[0047] In some embodiments of the present invention, the pore size of mesoporous titanium dioxide is 3-12 nm; in some specific embodiments of the present invention, the pore size of mesoporous titanium dioxide is 3.5-10 nm; in some examples of the present invention, the pore size of mesoporous titanium dioxide is 4-8 nm. Non-limiting specific examples are 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm or 7.5 nm.

[0048] In some embodiments of the present invention, the pore volume of mesoporous titanium dioxide is 20 to 35 m 3 / g; In some specific embodiments of the present invention, the pore volume of mesoporous titanium dioxide is 21 to 32 m 3 / g; In some examples of the present invention, the pore volume of mesoporous titanium dioxide is 22 to 30 m 3 / g. Non-limiting specific examples include 23m 3 / g, 24m 3 / g, 25m 3 / g, 26m 3 / g, 27m 3 / g, 28m 3 / g or 29m 3 / g.

[0049] Mesoporous titanium dioxide with appropriate pore size and pore volume is beneficial to improving the antibacterial rate and long-term antibacterial effect of the material. If the pore size and pore volume of mesoporous titanium dioxide are too small, Ag + With Zn 2+ It is difficult to enter the mesoporous structure of mesoporous titanium dioxide, Ag + With Zn 2+ The loading amount is small and the antibacterial property is poor; if the pore size and pore volume of mesoporous titanium dioxide are too large, Ag + With Zn 2+ The release rate is too fast, which affects the long-term antibacterial rate of the material.

[0050] In some embodiments of the present invention, the average particle size of mesoporous titanium dioxide is 20-150 nm; in some specific embodiments of the present invention, the average particle size of mesoporous titanium dioxide is 30-120 nm; in some examples of the present invention, the average particle size of mesoporous titanium dioxide is 40-100 nm. Non-limiting specific examples are 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0051] In some embodiments of the present invention, the mesoporous structure of the mesoporous titanium dioxide is loaded with silver ions and zinc ions at the same time.

[0052] Mesoporous titanium dioxide loaded with silver ions and zinc ions has better antibacterial effect. + 、Zn 2+ It has a better coordination effect. If there is only a single inorganic antibacterial agent, the antibacterial effect will be reduced.

[0053] In some embodiments of the present invention, the silver ion content in the composite antibacterial agent is 9-16wt%; in some specific embodiments of the present invention, the silver ion content in the composite antibacterial agent is 10-15wt%; in some embodiments of the present invention, the silver ion content in the composite antibacterial agent is 11-14wt%; non-limiting specific examples are 11.2wt%, 11.5wt%, 11.8wt%, 12wt%, 12.2wt%, 12.5wt% or 12.8wt%.

[0054] In some embodiments of the present invention, the zinc ion content in the composite antibacterial agent is 14-20wt%; in some specific embodiments of the present invention, the zinc ion content in the composite antibacterial agent is 15-19wt%; in some embodiments of the present invention, the zinc ion content in the composite antibacterial agent is 16-18wt%; non-limiting specific examples are 16.2wt%, 16.5wt%, 16.8wt%, 17wt%, 17.2wt%, 17.5wt% or 17.8wt%.

[0055] In some embodiments of the present invention, the composite antibacterial agent is prepared by a method comprising the following steps: mixing silver salt and / or zinc salt with mesoporous titanium dioxide, and then subjecting the mixture to pressure treatment to obtain the composite antibacterial agent.

[0056] In some embodiments of the present invention, in the preparation method of the composite antibacterial agent, the pressure of the pressurized treatment is 6 to 14 MPa; in some specific embodiments of the present invention, the pressure of the pressurized treatment is 7 to 13 MPa; in some examples of the present invention, the pressure of the pressurized treatment is 8 to 12 MPa. Non-limiting specific examples are 8.5 MPa, 9 MPa, 9.5 MPa, 10 MPa, 10.5 MPa, 11 MPa or 11.5 MPa.

[0057] In some embodiments of the present invention, in the preparation method of the composite antibacterial agent, the temperature of the pressurized treatment is 60-140°C; in some specific embodiments of the present invention, the temperature of the pressurized treatment is 70-130°C; in some examples of the present invention, the temperature of the pressurized treatment is 80-120°C. Non-limiting specific examples are 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or 115°C.

[0058] In some embodiments of the present invention, in the preparation method of the composite antibacterial agent, the time of pressurization treatment is 2 to 10 hours; in some specific embodiments of the present invention, the time of pressurization treatment is 3 to 9 hours; in some examples of the present invention, the time of pressurization treatment is 4 to 8 hours. Non-limiting specific examples are 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours or 7.5 hours.

[0059] In some embodiments of the present invention, in the method for preparing the composite antibacterial agent, the method for mixing the raw materials is selected from stirring.

[0060] In some embodiments of the present invention, in the method for preparing the composite antibacterial agent, the speed of mixing the raw materials is 50 to 150 rpm; non-limiting specific examples are 60 rpm, 80 rpm, 100 rpm, 120 rpm or 140 rpm.

[0061] In some embodiments of the present invention, in the method for preparing the composite antibacterial agent, the time for mixing the raw materials is 8 to 12 hours; non-limiting specific examples are 9 hours, 10 hours or 11 hours.

[0062] In some embodiments of the present invention, the amount of the composite antibacterial agent is selected from 0.6 to 1.8 parts by mass; in some specific embodiments of the present invention, the amount of the composite antibacterial agent is selected from 0.7 to 1.6 parts by mass; in some examples of the present invention, the amount of the composite antibacterial agent is selected from 0.8 to 1.5 parts by mass; non-limiting specific examples are 0.9 parts, 1 part, 1.1 parts, 1.2 parts, 1.3 parts or 1.4 parts.

[0063] The composite antibacterial agent of the present invention has good antibacterial performance, can achieve high-efficiency and long-lasting antibacterial effect when used in a relatively small amount, and can also ensure good mechanical properties of the material.

[0064] In some embodiments of the present invention, the silver salt is selected from water-soluble silver salts; in some specific embodiments of the present invention, the silver salt includes at least one of silver nitrate, silver fluoride, silver chlorate or silver perchlorate; in some examples of the present invention, the silver salt is selected from silver nitrate.

[0065] In some embodiments of the present invention, the zinc salt is selected from water-soluble zinc salts; in some specific embodiments of the present invention, the zinc salt includes at least one of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or zinc carbonate; in some examples of the present invention, the zinc salt is selected from zinc nitrate.

[0066] In some embodiments of the present invention, the average particle size of the composite antibacterial agent is 20 to 150 nm; in some specific embodiments of the present invention, the average particle size of the composite antibacterial agent is 30 to 120 nm; in some examples of the present invention, the average particle size of the composite antibacterial agent is 40 to 100 nm. Non-limiting specific examples are 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0067] In some embodiments of the present invention, the scratch resistant agent includes an amide scratch resistant agent, a silicone scratch resistant agent or a combination thereof; in some specific embodiments of the present invention, the scratch resistant agent is selected from silicone scratch resistant agents; in some examples of the present invention, the silicone scratch resistant agent is selected from polysiloxane.

[0068] In the system of the present invention, the use of an organosilicon-based scratch-resistant agent has better compatibility and can obtain a modified polypropylene material with better scratch-resistant performance.

[0069] In some embodiments of the present invention, the average particle size of the spherical inorganic filler is 400-700 nm; in some specific embodiments of the present invention, the average particle size of the spherical inorganic filler is 450-650 nm; in some examples of the present invention, the average particle size of the spherical inorganic filler is 500-600 nm. Non-limiting specific examples are 520 nm, 540 nm, 550 nm, 560 nm or 580 nm.

[0070] In some embodiments of the present invention, the density of the spherical inorganic filler is 0.5-3 g / cm 3 In some specific embodiments of the present invention, the density of the spherical inorganic filler is 0.8 to 2.5 g / cm 3 In some examples of the present invention, the density of the spherical inorganic filler is 1 to 2 g / cm 3 . Non-limiting specific examples include 1.2 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 or 1.8 g / cm 3 .

[0071] In some embodiments of the present invention, the spherical inorganic filler includes at least one of calcium carbonate, glass beads, silicon dioxide, boron nitride, silicate, aluminum oxide or titanium dioxide; in some specific embodiments of the present invention, the spherical inorganic filler is selected from calcium carbonate.

[0072] In some embodiments of the present invention, the filler further comprises a non-spherical inorganic filler.

[0073] The filler of the present invention may contain non-spherical inorganic fillers in addition to spherical inorganic fillers, that is, a combination of spherical inorganic fillers and non-spherical inorganic fillers may be used. However, compared with non-spherical inorganic fillers, spherical inorganic fillers can be more effectively dispersed in the matrix material of the present invention to form a more uniform and dense composite structure, and can achieve better mechanical properties such as tensile strength, bending strength and impact strength. Therefore, the present invention uses spherical inorganic fillers to have a better reinforcement effect.

[0074] In some embodiments of the present invention, the non-spherical inorganic filler includes talc, silica fume or a combination thereof.

[0075] In some embodiments of the present invention, the compatibilizer includes a maleic anhydride grafted polymer; in some specific embodiments of the present invention, the compatibilizer is selected from a maleic anhydride grafted polymer.

[0076] In some embodiments of the present invention, the maleic anhydride grafting rate of the maleic anhydride grafted polymer is 0.8-2.5 wt %; in some specific embodiments of the present invention, the maleic anhydride grafting rate of the maleic anhydride grafted polymer is 1-2 wt %; in some examples of the present invention, the maleic anhydride grafting rate of the maleic anhydride grafted polymer is 1.2-1.8 wt %. Non-limiting specific examples include 1.3 wt %, 1.4 wt %, 1.5 wt %, 1.6 wt % or 1.7 wt %.

[0077] In some embodiments of the present invention, the maleic anhydride grafted polymer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene or maleic anhydride grafted polyolefin elastomer; in some specific embodiments of the present invention, the maleic anhydride grafted polymer is selected from maleic anhydride grafted polypropylene.

[0078] In some embodiments of the present invention, the modified polypropylene material includes the following raw materials in proportion by weight: 60 to 85 parts of polypropylene resin; 8 to 20 parts of filler; 2 to 5 parts of compatibilizer; 1 to 2.8 parts of anti-scratch agent; 0.6 to 1.8 parts of composite antibacterial agent; and 0.2 to 1.5 parts of functional additive.

[0079] In some specific embodiments of the present invention, the modified polypropylene material includes the following raw materials in parts by weight: 70 to 83 parts of polypropylene resin; 10 to 18 parts of filler; 3 to 4 parts of compatibilizer; 1.5 to 2.5 parts of anti-scratch agent; 0.8 to 1.5 parts of composite antibacterial agent; and 0.3 to 1 part of functional additive.

[0080] In some embodiments of the present invention, the functional aid includes an antioxidant, a lubricant, or a combination thereof; in some embodiments of the present invention, the functional aid includes an antioxidant and a lubricant.

[0081] In some embodiments of the present invention, the antioxidant includes at least one of a hindered phenol antioxidant, a hydroxylamine antioxidant or a phosphite antioxidant; in some specific embodiments of the present invention, the antioxidant includes a hindered phenol antioxidant, a phosphite antioxidant or a combination thereof; in some examples of the present invention, the antioxidant includes a hindered phenol antioxidant and a phosphite antioxidant.

[0082] In some embodiments of the present invention, the hindered phenol antioxidant includes at least one of antioxidant 1010 , antioxidant 1076 , or antioxidant 1330 .

[0083] In some embodiments of the present invention, the phosphite antioxidant includes at least one of antioxidant 168 , antioxidant 626 , or antioxidant 618 .

[0084] In some embodiments of the present invention, the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, antioxidant 1330, antioxidant 168, antioxidant 626 or antioxidant 618; in some specific embodiments of the present invention, the antioxidant includes antioxidant 1010, antioxidant 168 or a combination thereof; in some examples of the present invention, the antioxidant includes antioxidant 1010 and antioxidant 168.

[0085] In some embodiments of the present invention, the antioxidant includes antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:(1-5); in some specific embodiments of the present invention, the mass ratio of antioxidant 1010 to antioxidant 168 is 1:(1.5-3); non-limiting specific examples are 1:1.8, 1:2 or 1:2.5.

[0086] In some embodiments of the present invention, the amount of the antioxidant is selected from 0.05 to 1 part by mass; in some specific embodiments of the present invention, the amount of the antioxidant is selected from 0.1 to 0.7 parts by mass; in some examples of the present invention, the amount of the antioxidant is selected from 0.1 to 0.4 parts by mass.

[0087] In some embodiments of the present invention, the lubricant includes at least one of a fatty acid lubricant, a hydrocarbon lubricant or an ester lubricant; in some specific embodiments of the present invention, the lubricant includes a fatty acid lubricant, a hydrocarbon lubricant or a combination thereof; in some examples of the present invention, the lubricant includes a fatty acid lubricant and a hydrocarbon lubricant.

[0088] In some embodiments of the present invention, the fatty acid lubricant includes at least one of stearic acid, magnesium stearate, calcium stearate or ethylene bis stearamide.

[0089] In some embodiments of the present invention, the hydrocarbon lubricant includes at least one of polyethylene wax, paraffin wax, or mineral oil.

[0090] In some embodiments of the present invention, the lubricant includes at least one of polyethylene wax, paraffin, mineral oil, stearic acid, magnesium stearate, calcium stearate or ethylene bisstearamide; in some specific embodiments of the present invention, the lubricant includes at least one of polyethylene wax, magnesium stearate, calcium stearate or ethylene bisstearamide; in some examples of the present invention, the lubricant includes polyethylene wax and calcium stearate.

[0091] In some embodiments of the present invention, the lubricant includes polyethylene wax and calcium stearate, and the mass ratio of polyethylene wax to calcium stearate is (1-5):1; in some specific embodiments of the present invention, the mass ratio of polyethylene wax to calcium stearate is (1.5-3):1; non-limiting specific examples are 1.8:1, 2:1, 2.2:1 or 2.5:1.

[0092] In some embodiments of the present invention, the amount of lubricant is selected from 0.05 to 1 parts by mass; in some specific embodiments of the present invention, the amount of lubricant is selected from 0.1 to 0.8 parts by mass; in some examples of the present invention, the amount of lubricant is selected from 0.2 to 0.6 parts by mass.

[0093] In some embodiments of the present invention, the modified polypropylene material includes the following raw materials in proportion by weight: 50 to 90 parts of polypropylene resin; 5 to 25 parts of filler; 1 to 6 parts of compatibilizer; 0.5 to 3 parts of anti-scratch agent; 0.5 to 2 parts of composite antibacterial agent; 0.05 to 1 part of antioxidant; and 0.05 to 1 part of lubricant.

[0094] In some specific embodiments of the present invention, the modified polypropylene material includes the following raw materials in proportion by weight: 60 to 85 parts of polypropylene resin; 8 to 20 parts of filler; 2 to 5 parts of compatibilizer; 1 to 2.8 parts of anti-scratch agent; 0.6 to 1.8 parts of composite antibacterial agent; 0.1 to 0.7 parts of antioxidant; and 0.1 to 0.8 parts of lubricant.

[0095] In some examples of the present invention, the modified polypropylene material includes the following raw materials in parts by weight: 70 to 83 parts of polypropylene resin; 10 to 18 parts of filler; 3 to 4 parts of compatibilizer; 1.5 to 2.5 parts of anti-scratch agent; 0.8 to 1.5 parts of composite antibacterial agent; 0.1 to 0.4 parts of antioxidant; and 0.2 to 0.6 parts of lubricant.

[0096] The second aspect of the embodiment of the present invention provides a method for preparing the modified polypropylene material of the first aspect of the embodiment of the present invention, comprising the following steps: mixing other preparation raw materials of the modified polypropylene material except the filler, adding the mixture to the main feed port of a twin-screw extruder, adding the filler to the side feed port of the twin-screw extruder, and extruding to obtain the modified polypropylene material.

[0097] In some embodiments of the present invention, the processing temperature of extrusion molding is 150-220°C; in some specific embodiments of the present invention, the processing temperature of extrusion molding is 160-200°C.

[0098] In some embodiments of the present invention, during extrusion molding, the temperature of zone one is 160-170°C, the temperature of zone two is 170-180°C, the temperature of zone three is 180-190°C, the temperature of zone four is 190-200°C, the temperature of zone five is 200-210°C, the temperature of zone six is ​​190-200°C, and the temperature of the die head is 190-200°C.

[0099] In some embodiments of the present invention, the extrusion molding is performed in the form of screw extrusion.

[0100] In some embodiments of the present invention, the aspect ratio of the screw is (45-60):1; in some specific embodiments of the present invention, the aspect ratio of the screw is (48-58):1; in some examples of the present invention, the aspect ratio of the screw is (50-55):1. Non-limiting specific examples are 51:1, 52:1, 53:1 or 54:1.

[0101] In some embodiments of the present invention, the screw speed is 250-500 rpm; in some specific embodiments of the present invention, the screw speed is 280-480 rpm; in some examples of the present invention, the screw speed is 300-450 rpm. Non-limiting specific examples are 320 rpm, 350 rpm, 380 rpm, 400 rpm or 420 rpm.

[0102] In some embodiments of the present invention, the extrusion molding is carried out under vacuum, and the vacuum degree of the extrusion molding is ≥0.08 MPa; in some specific embodiments of the present invention, the vacuum degree of the extrusion molding is 0.08-0.3 MPa. Non-limiting specific examples are 0.1 MPa, 0.12 MPa, 0.15 MPa, 0.18 MPa, 0.2 MPa or 0.25 MPa.

[0103] In some embodiments of the present invention, in the preparation method of modified polypropylene material, the speed of mixing the various raw materials is 200-400rpm; in some specific embodiments of the present invention, the speed of mixing the various raw materials is 220-350rpm; non-limiting specific examples are 230, 250rpm, 270rpm, 300rpm or 320rpm.

[0104] In some embodiments of the present invention, in the preparation method of the modified polypropylene material, the time for mixing the various preparation raw materials is 5 to 15 minutes; in some specific embodiments of the present invention, the time for mixing the various preparation raw materials is 7 to 13 minutes; non-limiting specific examples are 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes.

[0105] In some embodiments of the present invention, in the preparation method of the modified polypropylene material, a granulation step is included after extrusion molding; in some specific embodiments of the present invention, the granulation method is selected from rotary pelletizing; in some examples of the present invention, the rotation speed of the rotary pelletizing is 10 to 25 rpm, non-limiting specific examples such as 12 rpm, 15 rpm, 20 rpm or 22 rpm.

[0106] In some embodiments of the present invention, the method for preparing modified polypropylene material further includes a screening step after granulation; in some specific embodiments of the present invention, the aperture of the sieve used for screening is 4 to 8 mm, with non-limiting specific examples such as 5 mm, 6 mm or 7 mm.

[0107] A third aspect of the embodiments of the present invention provides a use of the modified polypropylene material of the first aspect of the embodiments of the present invention in the preparation of automobile parts.

[0108] In some embodiments of the present invention, the automobile component includes at least one of an automobile interior component, an automobile exterior component or an automobile structural component; in some specific embodiments of the present invention, the automobile component is selected from an automobile interior component.

[0109] In some embodiments of the present invention, the automobile interior component includes at least one of an automobile armrest, an automobile handle, a steering wheel, or an instrument panel.

[0110] The present invention is further described below in conjunction with specific embodiments and comparative examples.

[0111] In the following examples and comparative examples, the raw materials used include the following:

[0112] High modulus polypropylene resin: PPH-MM20S (flexural modulus is 2200MPa), CNOOC Shell;

[0113] Ordinary homopolymer polypropylene resin: EP300M-Z (flexural modulus is 1300MPa), CNOOC Shell;

[0114] Nano calcium carbonate: 471-34-1 (spherical, average particle size 550nm, density 1.2g / cm 3 ), Huishun Mining Co., Ltd.;

[0115] Wollastonite powder: 627-20-3 (rod-shaped, silicon content 49%, particle size 580-650nm, density 2.1g / cm 3 ), Micro-source Technology;

[0116] Maleic anhydride grafted polypropylene: KT-1 (grafting rate 1.2%), Yitian New Materials;

[0117] Mesoporous titanium dioxide: SS-S514JK (diameter 50nm, pore size 5nm, pore volume 23m 3 / g), Jikang New Materials;

[0118] Mesoporous titanium dioxide: SS-S518JK (diameter 50nm, pore size 2nm, pore volume 18m 3 / g), Jikang New Materials;

[0119] Silver nitrate solution: R049639 (concentration 0.025 mol / L), Haibo Biotechnology;

[0120] Zinc nitrate solution: Y073728 (concentration 0.025 mol / L), Haibo Biotechnology;

[0121] Composite antibacterial agent: (self-made, tested: silver ion content is 12.5±0.4wt%, zinc ion content is 16.7±0.6wt%, average particle size is 50nm);

[0122] Polysiloxane: HG-600S, Solvay High-tech Materials;

[0123] Erucamide: 10094-45-8, Microbiotech;

[0124] Antioxidants: Antioxidant 1010, Antioxidant 168, BASF;

[0125] Lubricant: Polyethylene wax (BN500), Bonnie Chemical; Calcium stearate (CV500), Hanwei;

[0126] Silica silver ion antibacterial powder: HN-S07 (silver content is 3.8±0.2%, average particle size is 100nm), Hengna New Materials.

[0127] Example 1

[0128] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0129]

[0130] The preparation method of the modified polypropylene material of this example is as follows:

[0131] 1) Preparation of composite antibacterial agent: 20 g of mesoporous titanium dioxide (SS-S500JK) was added to a mixed solution of 60 mL of silver nitrate (R049639) and 60 mL of zinc nitrate (Y073728), the stirring speed was controlled to be 120 rpm, and after 10 hours, the mixture was filtered to retain the solid matter, and then the solid matter was placed in a pressurized box for pressurization, the temperature of the pressurized box was controlled to be 95 ° C, the pressure was 10 MPa, and the pressurization time was continued for 6 hours to finally obtain the composite antibacterial agent;

[0132] 2) Pour high modulus polypropylene resin, compatibilizer, composite antibacterial agent, anti-scratch agent, antioxidant and lubricant into a mixer, set the mixing speed of the mixer to 250 rpm, the mixing time to 10 min, and pour into the main feeding port of the twin-screw extruder after blending evenly, and add the filler into the side feeding port of the twin-screw extruder;

[0133] 3) Control the temperature of the first zone of the twin-screw extruder to 160°C, the temperature of the second zone to 170°C, the temperature of the third zone to 180°C, the temperature of the fourth zone to 190°C, the temperature of the fifth zone to 200°C, the temperature of the sixth zone to 200°C, and the temperature of the die head to 190°C, haul off the material, cut it into pellets with a pelletizer, remove the particles and powder that do not meet the specifications after passing through a vibrating screen, mix them evenly in the finished product bin, and obtain the standard particles of the modified polypropylene material in this example. The aspect ratio of the twin-screw extruder is 52:1, the main engine speed is 350rpm, the vacuum degree is ≥0.08MPa, the pelletizer speed is 15rpm, and the vibrating screen is a linear double-axis vibrating screen with an aperture of 6mm.

[0134] Example 2

[0135] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0136]

[0137]

[0138] The difference between this example and Example 1 is that the mass portion of the scratch resistant agent (polysiloxane HG-600S) used in this example is increased to 2 parts, and the relevant weight difference is subtracted from the polypropylene resin (PPH-MM20S) in the formula. The remaining raw materials and preparation methods are the same as those in Example 1.

[0139] Example 3

[0140] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0141]

[0142] The difference between this example and Example 1 is that the composite antibacterial agent used in this example is reduced to 1.0 part, and the relevant amount difference is supplemented by the polypropylene resin (PPH-MM20S) in the formula. The remaining raw materials and preparation method are the same as those in Example 1.

[0143] Example 4

[0144] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0145]

[0146] The difference between this example and Example 1 is that the filler (nano calcium carbonate TC-1016) used in this example is reduced to 11 parts, and the relevant amount difference is supplemented by the polypropylene resin (PPH-MM20S) in the formula. The remaining raw materials and preparation method are the same as those in Example 1.

[0147] Example 5

[0148] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0149]

[0150] The difference between this example and Example 1 is that the preparation method of the composite antibacterial agent in this example is as follows:

[0151] 20g of mesoporous titanium dioxide (SS-S500JK) was put into 60mL of silver nitrate (R049639) solution, the stirring speed was controlled to be 120rpm, and after 10h, the solid was filtered and retained, and then the solid was placed in a pressurized box for pressurization, the temperature of the pressurized box was controlled to be 95°C, the pressure was 10MPa, and the pressurization time was continued for 6h to finally obtain a composite antibacterial agent. The rest of the raw materials and preparation method are the same as those in Example 1.

[0152] Example 6

[0153] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0154]

[0155] The difference between this example and Example 1 is that in the composite antibacterial agent of this example, the mesoporous titanium dioxide (SS-S518JK) used has a particle diameter of 50 nm, a pore size of 2 nm, and a pore volume of 18 m 3 / g, and the remaining raw materials and preparation method are the same as those in Example 1.

[0156] Example 7

[0157] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0158]

[0159]

[0160] The difference between this example and Example 1 is that the anti-scratch agent in this example is erucic acid amide (10094-45-8), and the remaining raw materials and preparation method are the same as those in Example 1.

[0161] Comparative Example 1

[0162] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0163]

[0164] The difference between this example and Example 1 is that this example uses ordinary polypropylene resin (EP300M-Z) with a flexural modulus of 1300 MPa, and the remaining raw materials and preparation method are the same as those in Example 1.

[0165] Comparative Example 2

[0166] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0167]

[0168] The difference between this example and Example 1 is that in this example, no composite antibacterial agent is added, and the relevant amount difference is supplemented by the polypropylene resin (PPH-MM20S) in the formula. The remaining raw materials and preparation method are the same as those in Example 1.

[0169] Comparative Example 3

[0170] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0171]

[0172]

[0173] The difference between this example and Example 1 is that the filler in this example is a rod-shaped wollastonite powder (627-20-3) filler, and the remaining raw materials and preparation method are the same as those in Example 1.

[0174] Comparative Example 4

[0175] A modified polypropylene material is prepared from the following raw materials in parts by weight:

[0176]

[0177] The difference between this example and Example 1 is that the composite antibacterial agent in this example uses commercially available silica-supported silver ion antibacterial powder (HN-S07), and the remaining raw materials and preparation method are the same as those in Example 1.

[0178] Performance Testing

[0179] The modified polypropylene materials obtained in Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to the following performance tests:

[0180] 1) Density: tested in accordance with ASTM D792-2020;

[0181] 2) Tensile strength and elongation at break: tested in accordance with ASTM D638-2022;

[0182] 3) Flexural strength and flexural modulus: tested in accordance with ASTM D790-2017;

[0183] 4) Impact strength: tested in accordance with ASTM D256-2023 standard;

[0184] 5) Antibacterial performance: According to GB / T 31402-2023, the antibacterial rate of each test sample (the antibacterial rate against Escherichia coli) was examined; Long-term antibacterial performance test: After the test sample was irradiated under a xenon lamp for 1400 hours, the antibacterial rate of each test sample (the antibacterial rate against Escherichia coli) was examined;

[0185] 6) Scratch resistance: The scratch resistance test is carried out according to the standard PV 3952-2002 with a load of 10N. The scratch resistance is judged by measuring the △L value (i.e. the change mark of black and white color) of the scratch test surface. The smaller the △L value, the better the scratch resistance of the material.

[0186] The test results of the modified polypropylene materials properties of Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 1.

[0187] Table 1 Performance test results of modified polypropylene materials of Examples 1 to 7 and Comparative Examples 1 to 4

[0188]

[0189] From the above test data, we can know that:

[0190] 1) It can be seen from the test results of Examples 1 to 7 and Comparative Examples 1 to 4 that the present invention, through the mutual coordination of the components in the formula, batch mixes the scratch resistant agent with the high modulus polypropylene, and simultaneously adds a homemade composite antibacterial agent, so that the prepared modified polypropylene material has excellent scratch resistance and excellent antibacterial properties.

[0191] In the embodiment, nano-scale mesoporous titanium dioxide is used to load Ag + With Zn 2+ A composite antibacterial agent was prepared, in which titanium dioxide itself has antibacterial properties and is then combined with an inorganic antibacterial agent Ag. + With Zn 2+ After the combination, the antibacterial performance is further improved; and the use of mesoporous titanium dioxide and pressurization can make more Ag + With Zn 2+ Loaded inside the mesoporous titanium dioxide particles, Ag + With Zn 2+ It will be slowly released through the mesopores on the surface of titanium dioxide to achieve the purpose of high efficiency and long-lasting antibacterial. After 1400 hours of xenon lamp irradiation, the antibacterial rate of the polypropylene material in Example 1 only decreased by 3.4%. In Example 2, the amount of scratch-resistant agent added is relatively large and the amount of high modulus polypropylene is relatively small. The scratch resistance and mechanical properties are basically equivalent. It can be seen that high modulus polypropylene itself has high hardness and scratch resistance. Selecting high modulus polypropylene as the substrate can reduce the amount of scratch-resistant agent while maintaining scratch resistance. When the amount of the composite antibacterial agent added in Example 3 is only 1 part, the modified polypropylene material has a good antibacterial effect, and when the amount of the composite antibacterial agent added is 1.2 parts, the modified polypropylene material can achieve excellent antibacterial properties, and the antibacterial rate can reach up to 99.9%. In Example 4, the amount of filler added is relatively small, and it still has good mechanical properties and antibacterial properties. It can be seen that the use of spherical nano-calcium carbonate as the filler of the present invention has a good enhancement effect. In Example 5, there is only a single inorganic antibacterial agent Ag. + , the antibacterial effect has decreased, which shows that the mesoporous titanium dioxide and the inorganic antibacterial agent Ag + 、Zn 2+ The pore size and pore volume of mesoporous titanium dioxide were changed in Example 6. It can be seen that the selection of the pore size and pore volume of mesoporous titanium dioxide will affect the antibacterial property of the modified polypropylene material. The reason is that the larger the pore size and pore volume of mesoporous titanium dioxide, the more Ag it can load. + With Zn 2+ , Ag + With Zn 2+ The higher the content, the better the antibacterial property; however, the pore size and pore volume of mesoporous titanium dioxide should not be too large, otherwise Ag + With Zn 2+The release rate is too fast, which affects the long-term antibacterial rate of the material. Example 7 uses erucamide as a scratch-resistant agent, which has good mechanical properties and antibacterial properties, but the scratch resistance is slightly reduced. The present invention uses polysiloxane to have a better scratch resistance effect.

[0192] 2) From the test results of Example 1 and Comparative Example 1, it can be seen that the scratch resistance of the composite material without high modulus polypropylene is far inferior to that of the composite material with high modulus polypropylene. The reason is that high modulus polypropylene itself has higher hardness and scratch resistance. Therefore, the amount of scratch resistance agent can be reduced while maintaining the scratch resistance.

[0193] 3) From the test results of Example 1 and Comparative Example 2, it can be seen that the antibacterial rate of the composite material without adding the antibacterial agent is 0, indicating that it has no antibacterial property; in addition, it can be seen that the addition of the composite antibacterial agent does not have a negative impact on the mechanical properties of the modified polypropylene material.

[0194] 4) It can be seen from the test results of the embodiment and comparative example 3 that the composite material using wollastonite powder as a filler has an increased density, but the tensile strength, flexural strength and impact strength are significantly lower than the composite material using nano-calcium carbonate filler. The reason is that nano-calcium carbonate is a spherical structure that can be more effectively dispersed in the matrix material to form a more uniform and dense composite structure. In contrast, wollastonite powder has a rod-like structure that is not easy to disperse, resulting in the formation of larger particle agglomerates in the composite material, which can become stress concentration points and reduce the mechanical properties of the material.

[0195] 5) From the test results of the embodiment and comparative example 4, it can be seen that the antibacterial rate of the composite material using the commercially available silica-supported silver ion antibacterial powder is only 81.7%, while the antibacterial rate of the composite material added with the self-made composite antibacterial agent of the present invention can reach up to 99.9%, and the antibacterial effect is excellent. The reason is that titanium dioxide itself has antibacterial properties, and when combined with the inorganic antibacterial agent Ag + With Zn 2+ After the combination, the antibacterial performance is further improved; in addition, after irradiation under a xenon lamp for 1400 hours, the antibacterial rate of the polypropylene material using the self-made composite antibacterial agent of the present invention only decreased by 3.4% at most, while the antibacterial rate of the polypropylene material using the silica-loaded silver ion antibacterial powder decreased by 13.3%; this is because the use of mesoporous titanium dioxide can make more Ag + With Zn 2+ Loaded inside titanium dioxide particles, Ag + With Zn 2+ It will be slowly released through the mesopores on the surface of titanium dioxide to achieve a highly efficient and lasting antibacterial effect.

[0196] From the above analysis, it can be seen that the embodiment of the present invention uses high modulus polypropylene resin as the base material, which can reduce the amount of scratch resistant agent while maintaining scratch resistance; mesoporous titanium dioxide with suitable pore size and pore volume is beneficial to improving the antibacterial rate and long-term antibacterial effect of the material, and the use of mesoporous titanium dioxide in combination with silver ions and zinc ions has a higher antibacterial rate, so that only a small amount of composite antibacterial agent needs to be added to enable the polypropylene material to achieve excellent antibacterial properties without reducing the mechanical properties of the polypropylene material; spherical inorganic fillers are used to make them more effectively dispersed in the matrix material, forming a more uniform and dense composite structure, and obtaining a material with higher strength; combined with maleic anhydride grafted polymer compatibilizer and silicone scratch resistant agent, the mechanical properties and scratch resistance of the material can be further improved.

[0197] The modified polypropylene material prepared in the embodiment of the present invention is an antibacterial, scratch-resistant, high-modulus polypropylene material, which has a high-efficiency and long-lasting antibacterial effect, and has excellent mechanical properties and scratch resistance, can extend the service life of the product, and can avoid harm to human health. It has a good application prospect in automotive parts, especially automotive interiors (such as automotive armrests).

[0198] In summary, the present invention selects high modulus polypropylene resin as the base material, and combines it with composite antibacterial agents, spherical inorganic fillers and other raw materials, which is beneficial for the material to have excellent mechanical properties and scratch resistance while maintaining high efficiency and lasting antibacterial effects.

Claims

1. A modified polypropylene material, characterized in that: The preparation method comprises the following raw materials in parts by weight: 50 to 90 parts of polypropylene resin; 5 to 25 parts of filler; 1 to 6 parts of compatibilizer; 0.5 to 3 parts of anti-scratch agent; 0.5 to 2 parts of composite antibacterial agent; 0.1 to 2 parts of functional additive; The flexural modulus of the polypropylene resin is ≥1900MPa; The filler includes a spherical inorganic filler; The composite antibacterial agent comprises mesoporous titanium dioxide, and the mesoporous structure of the mesoporous titanium dioxide is loaded with silver ions and / or zinc ions; the pore size of the mesoporous titanium dioxide is 1 to 15 nm, and the pore volume of the mesoporous titanium dioxide is 15 to 40 m 3 / g.

2. The modified polypropylene material according to claim 1, characterized in that: The silver ion content in the composite antibacterial agent is 9 to 16 wt %; And / or, the zinc ion content in the composite antibacterial agent is 14-20wt%.

3. The modified polypropylene material according to claim 1 or 2, characterized in that: The composite antibacterial agent is prepared by a method comprising the following steps: mixing silver salt and / or zinc salt with mesoporous titanium dioxide, and then performing a pressure treatment to obtain the composite antibacterial agent.

4. The modified polypropylene material according to claim 3, characterized in that: The pressure of the pressurized treatment is 6 to 14 MPa; And / or, the temperature of the pressure treatment is 60 to 140°C; And / or, the pressure treatment time is 2 to 10 hours.

5. The modified polypropylene material according to claim 1, characterized in that: The anti-scratch agent includes an amide anti-scratch agent, a silicone anti-scratch agent or a combination thereof.

6. The modified polypropylene material according to claim 1, characterized in that: The average particle size of the spherical inorganic filler is 400 to 700 nm; And / or, the density of the spherical inorganic filler is 0.5-3 g / cm 3 ; And / or, the spherical inorganic filler includes at least one of calcium carbonate, glass microspheres, silicon dioxide, boron nitride, silicate, aluminum oxide or titanium dioxide; And / or, the filler further includes a non-spherical inorganic filler, and the non-spherical inorganic filler includes talc powder, silica fume powder or a combination thereof.

7. The modified polypropylene material according to claim 1, characterized in that: The compatibilizer includes a maleic anhydride grafted polymer; Preferably, the maleic anhydride grafted polymer has a maleic anhydride grafting rate of 0.8-2.5 wt %; and / or the maleic anhydride grafted polymer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene or maleic anhydride grafted polyolefin elastomer.

8. The modified polypropylene material according to claim 1, characterized in that: The functional additives include antioxidants, lubricants or a combination thereof; Preferably, the amount of the antioxidant is selected from 0.05 to 1 part by mass; and / or the amount of the lubricant is selected from 0.05 to 1 part by mass.

9. A method for preparing the modified polypropylene material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified polypropylene material is prepared by mixing other raw materials except the filler, adding the mixture to the main feeding port of a twin-screw extruder, adding the filler to the side feeding port of the twin-screw extruder, and extruding to obtain the modified polypropylene material.

10. Use of the modified polypropylene material according to any one of claims 1 to 8 in the preparation of automobile parts.

Citation Information

Patent Citations

  • Scratch-resistant V0-grade halogen-free flame-retardant polypropylene material and preparation method thereof

    CN110684278A

  • Antibacterial titania

    JP1993004816A